Kynurenine 3-Monooxygenase Gene Associated With Nicotine Initiation and Addiction: Analysis of Novel Regulatory Features at 5′ and 3′-Regions - Aziz, Hassan A.; Abdel-Salam, Abdel-Salam G.; Al-Obaide, Mohammed A. I.; Alobydi, Hytham W.; Al-Humaish, Saif (Frontiers in Genetics, 2018)
Tobacco smoking is widespread behavior in Qatar and worldwide and is considered one of the major preventable causes of ill health and death. Nicotine is part of tobacco smoke that causes numerous health risks and is incredibly addictive; it binds to the α7 nicotinic acetylcholine receptor (α7nAChR) in the brain. Recent studies showed α7nAChR involvement in the initiation and addiction of smoking. Kynurenic acid (KA), a significant tryptophan metabolite, is an antagonist of α7nAChR. Inhibition of Kynurenine 3-monooxygenase enzyme encoded by KMO enhances the KA levels. Modulating KMO gene expression could be a useful tactic for the treatment of tobacco initiation and dependence. Since KMO regulation is still poorly understood, we aimed to investigate the 5' and 3'-regulatory factors of KMO gene to advance our knowledge to modulate KMO gene expression. In this study, bioinformatics methods were used to identify the regulatory sequences associated with expression of KMO. The displayed differential expression of KMO mRNA in the same tissue and different tissues suggested the specific usage of the KMO multiple alternative promoters. Eleven KMO alternative promoters identified at 5'-regulatory region contain TATA-Box, lack CpG Island (CGI) and showed dinucleotide base-stacking energy values specific to transcription factor binding sites (TFBSs). The structural features of regulatory sequences can influence the transcription process and cell type-specific expression. The uncharacterized LOC105373233 locus coding for non-coding RNA located on the reverse strand in a convergent manner at the 3'-side of KMO locus. The two genes likely expressed by a promoter that lacks TATA-Box harbors CGI and two TFBSs linked to the bidirectional transcription, the NRF1, and ZNF14 motifs. We identified two types of microRNA (miR) in the uncharacterized LOC105373233 ncRNA, which are like hsa-miR-5096 and hsa-miR-1285-3p can target the microRNA recognition element (MRE) in the KMO mRNA. Pairwise sequence alignment identified 52 nucleotides sequence hosting MRE in the KMO 3' UTR untranslated region complementary to the non-coding RNA LOC105373233 sequence. We speculate the identified microRNAs can modulate the KMO expression and together with alternative promoters at the 5'-regulatory region of KMO might contribute to the development of novel diagnostic and therapeutic algorithm for tobacco smoking.